Challenging Ethics and Moral Education in The Age of Technology Among Student in Bandung - Sarbini, Sarbini (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study aims to examine the challenges of ethical and moral education in the technological age among students. The study was conducted in Cipadung Village, Ujung Berung District, Bandung City by applying a qualitative approach and descriptive method. Data collection was carried out on 28 (twenty-eight) selected informants, 22 (twenty-two) students, 3 (three) teachers, and 3 (three) parents of students. Research finds that ethical and moral education among students in the technological age has great challenges. In addition to technology providing benefits for easy access to sources of information and learning, technology has many negative impacts. Students who are able to apply ethical and moral education in this technological age will be able to control technology as a learning medium. On the other hand, students who do not have sufficient ethical and moral education will be controlled by technology. This study concludes that educational and moral challenges relate to students' ability to apply them in the realities of life, especially in the technological age.